The Olympics and Japanese national identity: Multi-layered otherness in Tokyo 2016 and 2020. Issue 2 (3rd July 2019) - Tamaki, Taku
ABSTRACT: How are Japanese identity narratives constructed in the Tokyo 2016 campaign and the Tokyo 2020 bid and organisation? The earlier narratives of Tokyo 1940 and 1964 bids entailed invoking Western Otherness to emphasise Japan's Asian affinity while simultaneously emphasising Japan's un-Asian characteristics, effectively employing dual Otherness to tell the story of Japanese Self. Tokyo's position as a global city today means that Japanese Self is now constituted through multiple Otherness involving the West, Asia, as well as the primacy of Tokyo in opposition to the relative neglect of the periphery, constructing a more complex story of Otherness. There are concerns Tokyo is hoarding infrastructure investment ahead of Tokyo 2020, just as the regions affected by the March 2011 disasters require capital infusion, fuelling a sense of Tokyo versus the rest. Hence, on top of the residual dual Otherness that can still be witnessed, Tokyo 2020 grafts another layer of Otherness, this time at the domestic level. In this article, I explore identity narratives by policy elites and opinion leaders to show the complex nature of multi-layered Otherness in the Tokyo 2016 and 2020 bidding and organisation.